'I Went through Hell': Strategies for Kidnapping and Victims' Experiences in Nigeria. Issue 10 (25th November 2020) - Tade, Oludayo; Ojedokun, Usman A.; Aderinto, Adeyinka A.
ABSTRACT: Understanding the experiences of the victims of kidnapping when in captivity can provide useful data for designing public safety behavior programs. Such experiences when probed more deeply expose the trajectories of movements to kidnappers' den and circumstances under which victims negotiate their survival. Existing studies have not examined these dimensions of kidnapping experiences in Nigeria. Using newspaper coverage of kidnapping cases in Nigeria, this article utilizes 20 newspaper interviews of former victims. Findings show that victims were tortured, threatened with violence and death, and regularly relocated to different camps to keep them in captivity. Victims' telephones were used to contact their families and the 'emotions of agony' put relations in panic to source for the ransom demanded. Gender, social status of victims, and level of cooperation from victims as well as their relations influenced kidnappers' range of treatment of victims. Based on the findings, this article recommends public safety behavior advocacy and awareness campaigns by security agencies and government highlighting contemporary strategies being used by kidnappers that could reduce kidnapping in Nigeria.